Penerapan Metode Discovery Learning untuk Meningkatkan Hasil Belajar IPS Materi Interaksi Sosial di Kelas VII B SMP Negeri 16 Mataram - Dewi, Sri Rahma (Lembaga Yasin AlSys, 2022)
The purpose of this study was to find out the increase in social studies learning outcomes in Social Interaction through the Application of the Discovery Learning Method to Improve Results in Class VII B of SMP Negeri 16 Mataram for the 2019/2020 academic year. The subjects of this study were Class VII.B students of SMP Negeri 16 Mataram in the odd semester of the 2019/2020 academic year, with a total of 32 students. The results showed that research using the Discovery Learning model could increase the activity of teacher and student learning outcomes. This was evident from the results obtained in cycle I was 74.06, cycle II was 82.71 and in cycle III was 88.18 for student learning outcomes . So it can be concluded that the application of the Discovery Learning method improves learning outcomes Social Interaction Social Studies Class VII B students of Mataram 16 Public Middle School in the 2019/2020 academic year.